Analisis Tingkat Kerapatan Vegetas terhadap Sedimentasi Waduk Batutegi - Chairunnisa, Zulfa Harda; Ridwan, Ridwan; Amien, Elhamida Rezkia; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2025)
The Batutegi Reservoir is one of the vital infrastructures in Lampung Province, serving as a source of irrigation water, hydroelectric power, raw water, and flood control for the surrounding area. However, changes in vegetation density in the catchment area can affect the rate of erosion and sedimentation in the reservoir, which impacts the storage capacity and useful life of the Batutegi Reservoir. This study aims to analyse changes in vegetation density in the reservoir catchment area using Sentinel-2A imagery and to assess its impact on sedimentation and total suspended solids (TSS) levels in Batutegi Reservoir during the period 2015-2024. The methods used included NDVI and WRI image analysis with satellite image processing using SNAP and ArcMap software, as well as SWAT model simulation to predict erosion and sedimentation. The results showed a 37.41% decrease in high-density vegetation area and a 339.32% increase in low-density vegetation during the observation period. The highest TSS level was recorded in 2018 at 14.51 mg/l, in line with high rainfall due to the La Niña phenomenon. SWAT simulations indicate the highest increase in sedimentation load in the same year, reaching 2,587.90 tonnes/year, with the largest contribution coming from sub-catchment area number 71 and 75. The correlation between sedimentation values from SWAT and Sentinel-2A showed a determination coefficient (R²) of 0.917. This study confirms that a significant decrease in vegetation density exacerbates reservoir sedimentation. Regular monitoring of changes in vegetation density and reservoir water quality, particularly TSS values, is an important strategy for maintaining the useful life and capacity of the Batutegi Reservoir